(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Modern technology and education play an important part throughout the course of our life today. It is widely acknowledged as the primary source of economic expansion. A financial system that is technologically deficient can never grow in today’s world. This is because technology makes our tasks lot easier and less time demanding. The impact of technology may be felt in every conceivable sector. The goal of this research was to look at the evolution of education and current technology, as well as the good and bad effects. The intended participants in this research were instructors, and information was acquired using a survey. According to the demographic data acquired, 200 instructors in two age groups (22-35 & 36-50) responded to the questionnaire. We used SPSS software to do regression analysis after collecting the questionnaire. We used regression analysis to evaluate each possibility.